Evaluation of the National Adherence Guidelines for Chronic Diseases in South Africa : Patient Perspectives on Differentiated Care Models, 2017 - World Bank (World Bank, Washington, DC, 2017)
This report presents the result of the qualitative evaluation to understand the implementation of five adherence interventions from the patient perspective in four South African provinces. The research is part of the evaluation of the new Adherence Guidelines for HIV, TB and other chronic diseases. The study sought to answer four key questions: questions: 1. How does patient satisfaction with care at the intervention sites compare to the control sites among HIV positive patients? 2. What are the barriers to and facilitators of ART initiation and adherence among HIV-positive patients eligible for each intervention? 3. What are the strengths and weaknesses of each intervention for HIV positive patients from the patient perspective? 4. What additional strategies do patients feel would be helpful in improving treatment adherence? The report presents the triangulated qualitative and quantitative data from patient surveys and focus group discussions under each of the four questions. The results show that from the patient perspective, each intervention has promise and supported either ART initiation or adherence, however each could be improved. Detailed illustrative quotes are provided for each intervention according to the main themes identified. Specifically, patients had very positive feelings about Adherence Clubs and Decentralized Medication Delivery in focus group discussions.